PENGGUNAAN INFORMASI NON-KEUANGAN DALAM EVALUASI KINERJA LKP EMYLIA: PERSPEKTIF AKUNTANSI MANAJEMEN - Magfirah Wahyu Ramadhani (Parsimonia - Jurnal Ekonomi dan Bisnis, 2026)
This study aims to understand the types of non-financial information used, how such information is interpreted by management, and its role in supporting institutional performance evaluation. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation, and were analyzed using thematic analysis. The findings indicate that LKP Emylia has used non-financial information as a basis for performance evaluation in an informal and contextual manner. Such information helps management assess service quality, learning effectiveness, instructor performance, and participant success after completing the training program. However, the use of non-financial information has not been fully documented in a structured evaluation system. The contribution of this study lies in enriching management accounting literature in the context of non-formal education institutions by showing that non-financial information plays an important role in evaluating performance, service quality, and institutional sustainability.